Political Marketing Strategies Through Social Media Tools in Indonesia - Dhony Hardiyanto; Mahendra Wijaya; Ign. Agung Satyawan (Formosa Journal of Social Sciences (FJSS), 2023)
A precise political marketing strategy is required in order to prevail and ensure the success of political parties or the politicians they support. Political marketing is the practice of organizing activities in a practical, planned, and strategic manner with the goal of ensuring the success of a political party or candidate supported by a political party in achieving its various political goals. Conventional media, including print and electronic media, are typically utilized to conduct political marketing. Given that the current environment suggests a shift in the public's attention from traditional media to social media, it will be interesting to see how political parties and candidates adapt their efforts and strategies to use social media for their political marketing. The objective of this study, which employs a qualitative research technique based on litelatur review, is to examine the evolution and tactics used by political parties to conduct political marketing on social media. The findings of this study show that social media is now a platform with a very high number of users, indicating that the time has come for political parties to put into practice an effective strategy in political marketing through social media in order to be able to win over voters' sympathy and interest in political parties or candidates